Shrimp Shell-Based Solid-State Fermentation Promotes Dual Antibacterial and Cytotoxic Metabolite in Kocuria palustris 19C38A1 - Widyastuti Widyastuti; Fendi Setiawan; Ety Apriliana; Wawan A Setiawan; Peni Ahmadi (Pandawa Institute, 2026)
The growing impact of antimicrobial resistance (AMR) and cancer highlights the need to develop new and more effective therapeutic agents. Here, we explore a solid-state fermentation (SSF) strategy using shrimp-shell waste to stimulate secondary metabolite of marine Kocuria palustris 19C38A1. Bioautography-guided screening revealed that polar components of the extract (C38FA) showed antibacterial activity against multidrug-resistant Staphylococcus aureus (MIC = 250 µg/mL), The same fraction demonstrated pronounced cytotoxicity, inhibiting cell viability of A549 and HeLa cancer cells by 89% and 98%, respectively, at 100 μg mL-1 concentration, while showing weaker activity toward MCF-7 cells. Dereplication analysis using LC–MS/MS has annotated six putative metabolites such as terpendole B (1), p-hydroxyphenylacetylglutamic acid (2), istamycin C1 (3), lankacidin C (4), anthelmycin (5), and octacosa-hexaenoic acid (6) with mass accuracies within ±0.3 ppm. Notably, four of these compounds have well established antibacterial or cytotoxic properties, consistent with the dual in vitro bioactivity observed. ADME predictions suggested that compounds 1 and 2 are the most promising drug-like candidates, showing high gastrointestinal absorption and low cytochrome P450 liability. Furthermore, computational target prediction indicated potential interactions with proteases, kinases, oxidoreductases, and EGFR associated pathways, further hinting at their dual activity multifunctionality. Molecular docking suggested that compound 1 binds to FtsZ and EGFR, with predicted binding energies of -6.89 and -9.03 kcal/mol, respectively. Collectively, this work suggests that shrimp-shell waste can serve as a sustainable biogenic elicitor that induces marine actinobacteria to produce metabolites with dual pharmacological activities under SSF. These findings highlight a sustainable method for discovering potential dual activity antibacterial and anticancer bioactive compounds with therapeutic potential.